Network pharmacology prediction and experimental verification of Rhubarb-Peach Kernel promoting apoptosis in endometriosis - Zi Liao; Ya Lei; Li Peng; Xianyun Fu; Wei Wang; Dan Yang (BMC, 2023)
Abstract Background "Rhubarb-Peach Kernel" herb pair (RP) one of the most frequently used drug pairs, has been used in traditional medicine in China to treat inflammation and diseases associated with pain. Although it is widely used clinically and has a remarkable curative effect, the mechanism of RP treatment for endometriosis (EMs) remains unclear due to its complicated components. The aim of this study was to investigate the anti-endometriosis effect of RP, with emphasis on apoptosis via network pharmacology prediction, molecular docking and experimental verification. Methods The related ingredients and targets of RP in treating EMs were screened out using Traditional Chinese Medicine Systems Pharmacology (TCMSP), Tool for Molecular mechanism of Traditional Chinese Medicine (BATMAN-TCM), and GeneCards database. The data of the protein-protein interaction (PPI) network was obtained by the Search Tool for the Retrieval of Interaction Gene/Proteins (STRING) Database. The Metascape database was adopt for Kyoto encyclopedia of genes and genomes (KEGG) enrichment analysis. After that, the molecular docking of the main active ingredients and apoptosis targets was performed. Finally, the pro-apoptotic effect of RP was verified in hEM15a cells. Results A total of 32 RP compounds were collected. Forty-two matching targets were picked out as the correlative targets of RP in treating EMs. Among these, 18 hub targets including P53, CASP3 were recognized by the PPI network. KEGG enrichment analysis discovered that the regulation of apoptosis was one of the potential mechanisms of RP against EMs. Anthraquinone compounds, flavonoids, and triterpenes in RP were identified as crucial active ingredients, involved in the pro-apoptotic effect, which were confirmed subsequently by molecular docking. Additionally, it was verified that RP treatment promoted apoptosis and inhibited the proliferation of EMs cells (assessed by MTT and Flow cytometry). Moreover, the induction of apoptosis in treated EMs cells may be due to the regulation of apoptosis-related protein expression, including P53, BAX, and CASP3. Conclusions The results of our study demonstrated that RP may exert its therapeutic effects on EMs through the potential mechanism of promoting apoptosis. Anthraquinones, flavonoids and triterpenoids are the possible pro-apoptotic components in RP.